Structural and Virus Regulatory Insights Into Avian N6-Methyladenosine (m6A) Machinery - Bayoumi, Mahmoud; Rohaim, Mohammed A.; Munir, Muhammad (Frontiers in Cell and Developmental Biology, 2020)
The addition of a methyl group to the N6 position of adenosine (m6A) is the most common post-transcriptional RNA modification and it regulates most steps of RNA metabolism including splicing, stability, translation, nuclear-export and RNA structures. Beside cellular RNA, m6A modifications have also been detected on viral RNA. A range of recent studies have demonstrated the crucial roles of m6A in the virus-host interactions; however, m6A cellular machineries are only characterized in limited mammalian species. Herein, we aim to present comprehensive evolutionary insights in major m6A writers, erasers and readers and draw a comparative structural analysis between avian and mammalian m6A-associated machineries. The comparative collinearity on the chromosomal scale revealed that the majority of m6A-related genes were found less syntenic even among avian species. Genetic analysis of avian m6A erasers revealed a distinct phylogenetic clustering compared to mammalian orthologs and shared a weak percent (55%) identity with mammalian species. The overall comparative 3D structure analyses among different mammalian species were maintained through synonymous structural mutations. Unlike erasers, the putative 3D structures in the active sites as the aromatic cage in YTH-domain of YTHDC1 and two pivotal loops in MTD-domains in METTL3 exhibited structural alterations in chicken. In conjunction with in silico investigations, influenza virus significantly downregulated gene transcription of m6A writers and erasers, whereas m6A readers were moderately regulated in chicken fibroblasts. In the light of these findings, future detailed biochemical and crystallographic studies are warranted to define the roles of m6A machinery in regulating both viral and cellular RNA metabolism in avian species.